2019
DOI: 10.1159/000499083
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Nephrin as a Biomarker of Glomerular Maturation and Injury Is Associated with Acute Kidney Injury and Mortality in Critically Ill Neonates

Abstract: Background: Nephrin is a key component of the slit diaphragm of the glomerular podocyte, and increased urinary nephrin level may reflect glomerular injury. Objectives: To determine whether urinary nephrin is a useful biomarker of glomerular maturation and injury and whether it is associated with acute kidney injury (AKI) and neonatal intensive care unit (NICU) mortality in critically ill neonates. Methods: Urinary samples were serially collected in 234 neonates during NICU stay for measurements of nephrin, cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The diagnostic accuracy of urinary nephrin for detecting PE and diabetic nephropathy could therefore be extrapolated into use as a potential predictor of early glomerular injury, particularly in the setting of AKI. Recently, studies have emerged investigating the value of urinary nephrin for predicting AKI, particularly in critically ill neonates [66,67]. These studies concluded that urinary nephrin may well provide a marker for predicting AKI, demonstrating a diagnostic sensitivity of 62.5%, 61.5%, and specificity of 82.1%, 76.9% respectively at a cut-off point of NCR = 0.375 µg/mg, suggesting that urinary nephrin may give an early indication of podocyte damage as an indicator of those infants at risk of developing AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic accuracy of urinary nephrin for detecting PE and diabetic nephropathy could therefore be extrapolated into use as a potential predictor of early glomerular injury, particularly in the setting of AKI. Recently, studies have emerged investigating the value of urinary nephrin for predicting AKI, particularly in critically ill neonates [66,67]. These studies concluded that urinary nephrin may well provide a marker for predicting AKI, demonstrating a diagnostic sensitivity of 62.5%, 61.5%, and specificity of 82.1%, 76.9% respectively at a cut-off point of NCR = 0.375 µg/mg, suggesting that urinary nephrin may give an early indication of podocyte damage as an indicator of those infants at risk of developing AKI.…”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that urinary nephrin may well provide a marker for predicting AKI, demonstrating a diagnostic sensitivity of 62.5%, 61.5%, and specificity of 82.1%, 76.9% respectively at a cut-off point of NCR = 0.375 µg/mg, suggesting that urinary nephrin may give an early indication of podocyte damage as an indicator of those infants at risk of developing AKI. This is an area of intense interest in the literature [30,66,67], since a single biomarker may not suffice to define AKI given inherent renal heterogeneity and the disparate settings under which kidney injury occurs [68].…”
Section: Discussionmentioning
confidence: 99%
“…Reports have described nephrin as a biomarker of AKI in NICU settings. A study enrolling newborns concluded that initial urinary nephrin levels were higher in newborns with AKI than in newborns without AKI, indicating that increased nephrin levels might occur as a consequence of glomerular immaturity, particularly in preterm newborns 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin may become an important biomarker of early glomerular injury 50 and AKI in NICU settings, particularly for preterm newborns 51 .…”
Section: Nephrin Podocytes 50mentioning
confidence: 99%
See 1 more Smart Citation